FENOMENA CAPTION â€œTWITTER, PLEASE DO YOUR MAGIC!â€ MEMBANGKITKAN NETIZEN UNTUK MENOLONG - Fammy, Nahdah Salsabila; Bambang, Aa; Hapsari, Dian Tri (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2020)
This research discusses the social media Twitter, which can arouse awareness, and context sharing, which can make a tweet become viral and hotly discussed by many people, especially Twitter netizens. This research is motivated by the many uses of social media that tend to lead to actions that are inappropriate and negative. For this reason, the purpose of this study is to provide an explanation that the social media Twitter can inspire young people to provide information that is not only important but also provides profound and useful meaning. This study employs the qualitative research method and is based on phenomenology. Based on the results of this study, it is expected that the social media Twitter can get more positive feedback from the public, not only by helping others but also through other good things that can be followed by other Twitter users, especially the younger generation.